PATH-14. SURGICAL STRATEGY FOR LOWER GRADE GLIOMAS USING INTRAOPERATIVE RAPID MOLECULAR AND PATHOLOGICAL DIAGNOSIS - Nitta, Masayuki (Neuro Oncol, 2018)
INTRODUCTION: In the 2016 WHO classification, genetic information was introduced in the pathological diagnosis of gliomas, and the correlation between molecular subtype and prognosis has been shown. High extent of removal (EOR) provides survival benefit for some subtype of lower grade gliomas (LGGs), but it is often difficult to achieve both high EOR and preservation of brain function. Our institute has been working on intraoperative rapid molecular diagnosis of LGGs using HRM method for IDH mutation and immunostaining of p53/ATRX for 1p/19q codeletion for an intraoperative decesion making. We report the clinical results of patients with LGGs treated in our facility and discuss the significance of the surgical strategy based on intraoperative rapid molecular diagnosis. METHODS: In 366 cases (G2: 219 cases, G3: 147 cases) with newly diagnosed LGGs that could be classified according to 2016 WHO classification in our hospital (2004–2014), the relation between the EOR and prognosis was retrospectively analyzed. Accuracy of intraoperative rapid molecular diagnosis of IDH mutation and 1p/19q codeletion using HRM method and p53 /ATRX immunostaining was evaluated. Result: The 10-year survival rate of oligodendroglioma was 88% in G2 (121 cases), 80% in G3 (59 cases), the 10-year survival rate of DA-IDH mutant was 63% in G2 (66 cases), MST of G3 (46 cases) was 13.6 years, MST of DA - IDH wild-type was G2 (32 cases) 12.6 years, G3 (42 cases) 3.9 years. The EOR strongly correlated with prognosis in DA-IDH wild-type. The results of intraoperative IHC of p53/ATRX were 82.6% consistent with FISH based results of 1p/19q codeletion. The HRM results (55 cases) were 100% consistent with sequence based IDH mutation results. CONCLUSION: The prognosis and the significance of EOR was significantly different between subtypes in LGGs. Rapid intraoperative molecular diagnosis seems to be useful for determining the removal strategy in LGG surgery.